Usability of CHA2DS2VASC score in predicting the effectiveness and safety of pharmacological cardioversion – data from the multicenter cardioversion with intravenous ANTazoline study - Krzowski, Bartosz; Ozierański, Krzysztof; Peller, Michał; Wróbel, Wojciech; Miśkowiec, Dawid; Ćwiek-Rębowska, Edyta; Maciąg, Aleksander; Farkowski, Michał; Szołkiewicz, Marek; Ceynowa-Sielawko, Beata; Koziński, Marek; Wójcik, Maciej; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPharmacological cardioversion (PCV) is one of the therapeutic options within rhythm control strategies for atrial fibrillation (AF). Data on clinical determinants influencing its effectiveness and safety in real-world settings remain limited.MethodsThis study is a sub-analysis of the multicenter Cardioversion with Intravenous Antazoline in Atrial Fibrillation II (CANT II) registry. The registry retrospectively included consecutive patients with recent-onset AF undergoing urgent PCV in six Polish centers between 2019 and 2020. We analyzed 931 patients stratified according to CHA₂DS₂-VASc score: Group I (0–1 points; n = 194), Group II (2–4 points; n = 580), and Group III (≥5 points; n = 157). The primary endpoint was successful restoration of sinus rhythm within 12 h, and the secondary endpoint was a composite of adverse events (death, syncope, bradycardia, hypotension).ResultsThe median age was 69 years, 48% were men, and the median CHA₂DS₂-VASc score was 3. Antazoline was used in 59% of patients, amiodarone in 53%, and propafenone in 19%. Sinus rhythm was restored in 69%, 70%, and 64% of patients in Groups I, II, and III, respectively (p = 0.45). The overall adverse event rate was low (2.1%) and did not differ significantly between groups (p = 0.16). Antazoline was most effective in Group I, while propafenone showed higher efficacy in Group II.ConclusionsIn this retrospective sub-analysis of the CANT II registry, success of pharmacological cardioversion of AF is not associated with number of comorbidities as assessed by the CHA2DS2VASc score. PCV remains a feasible and generally safe option in emergency and cardiology department practice.